2007
DOI: 10.1103/physrevlett.99.036603
|View full text |Cite
|
Sign up to set email alerts
|

Noise Correlations in a Coulomb-Blockaded Quantum Dot

Abstract: We report measurements of current noise auto-and cross-correlation in a tunable quantum dot with two or three leads. As the Coulomb blockade is lifted at finite source-drain bias, the autocorrelation evolves from super-Poissonian to sub-Poissonian in the two-lead case, and the crosscorrelation evolves from positive to negative in the three-lead case, consistent with transport through multiple levels. Cross-correlations in the three-lead dot are found to be proportional to the noise in excess of the Poissonian … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
59
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 30 publications
3
59
1
Order By: Relevance
“…In our case, the current in the most interesting regime is proportional to t 2 x, where x is exponentially small in ⌬ / k B T. Since the tunneling amplitude t can, in principle, be made arbitrarily small, sequential tunneling becomes the dominant process. Recently, it was shown that noise spectroscopy deep inside the Coulomb-blockade regime is possible [23][24][25][26] and in agreement with the sequential-tunneling description.…”
Section: Model and Theoretical Methodsmentioning
confidence: 63%
“…In our case, the current in the most interesting regime is proportional to t 2 x, where x is exponentially small in ⌬ / k B T. Since the tunneling amplitude t can, in principle, be made arbitrarily small, sequential tunneling becomes the dominant process. Recently, it was shown that noise spectroscopy deep inside the Coulomb-blockade regime is possible [23][24][25][26] and in agreement with the sequential-tunneling description.…”
Section: Model and Theoretical Methodsmentioning
confidence: 63%
“…This was motivated by a number of reasons. First of all, such three-terminal setups share a number of features with mesoscopic Coulombdrag setups that have been studied both theoretically [60,61,62,63,64,65,66] as well as experimentally [67,68,69,70,71] in the last years. Such Coulomb-drag setups consist of two nearby mesoscopic conductors such as quantum dots.…”
Section: Introductionmentioning
confidence: 99%
“…Petta et al A method for determining spin coherence times using electrical transport through a quantum dot in the stationary state has been suggested by Engel and Loss [6], but this method can only determine coherence times up to an upper limit that is related to the temperature of the contacts. The study of current-current correlations has emerged as a tool to detect coherence properties of quantum systems such as quantum dots [7]. In nanomechanical resonators the noise power spectrum has been used to determine the oscillator occupation number and quality factor [8,9,10].…”
mentioning
confidence: 99%
“…The study of current-current correlations has emerged as a tool to detect coherence properties of quantum systems such as quantum dots [7]. In nanomechanical resonators the noise power spectrum has been used to determine the oscillator occupation number and quality factor [8,9,10].…”
mentioning
confidence: 99%